Determination of 5-hydroxymethylfurfural using an electropolymerized molecularly imprinted polymer in combination with Salle - Francisco, Karen C.A. [UNESP]; Lobato, Alnilan; Tasić, Nikola; Cardoso, Arnaldo A. [UNESP]; Gonçalves, Luís M. (Elsevier, 2022)
Coffee, a beverage with a complex chemical composition, is appreciated for the sensory experience of its taste and aroma. The compound 5-(hydroxymethyl)-2-furfural (HMF) is essential for sensory characterization of the beverage, and is also used in the traceability of its production. In this work, a procedure combining salting-out assisted liquid-liquid extraction (SALLE) and an electropolymerized molecularly imprinted polymer (e-MIP) was developed for the detection and quantification of HMF in coffee samples. The sample preparation step using SALLE employed a combination of acetonitrile and phosphate-buffered saline, in a proportion of 70:30 (ACN:PBS), with addition of 0.02 g of NaCl. The new sensor (e-MIP) was prepared by electropolymerization of p-aminobenzoic acid onto a glassy carbon electrode (GCE) using cyclic voltammetry (CV). Analytical determinations were performed by differential pulse voltammetry (DPV). The linear regression correlation coefficient (r2) for the response was 0.9986. The limits of detection and quantification were 0.372 mg L−1 and 1.240 mg L−1, respectively. The repeatability and reproducibility values obtained were 6 and 10%, respectively. The recoveries for three concentration levels were between 97 and 101%. Analyses of different coffee samples showed that the HMF concentrations varied from 261.0 ± 41.0 to 770.2 ± 55.9 mg kg−1 in powdered coffee samples, and from 1510 ± 50 to 4445 ± 278 mg kg−1 in instant coffee samples. The advantages of this procedure, compared to other methods described in the literature, are its simplicity, easy operation, good selectivity and sensitivity, low cost, and minimal use of organic solvents.
Keywords: 5-(Hydroxymethyl)-2-furfural; Electroanalysis; Electropolymerization; Molecular recognition; Salting-out assisted liquid-liquid extraction; Sample preparation